(untitled) (TAMADDUN NURI JURNALI, 2024)
The family rituals of the Uzbek people have been formed over centuries, enriched with modern elements and are developing. Any ceremony is a social reality, develops and improves. Family rituals of the Uzbek people are an axiological reality with their own moral evolutionary development and separate periods of development. In this article, a philosophical analysis is made of the need to introduce specific regulations in the development of national values ​​and to preserve the rituals in their true essence.